The long-term costs of government surveillance: Insights from Stasi spying in East Germany - Andreas Lichter; Max Löffler; Sebastian Siegloch (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
We investigate the long-run effects of government surveillance on civic capital and economic performance, studying the case of the Stasi in East Germany. Exploiting regional variation in the number of spies and administrative features of the system, we combine a border discontinuity design with an instrumental variables strategy to estimate the long-term, post-reunification effect of government surveillance. We find that a higher spying density led to persistently lower levels of interpersonal and institutional trust in post-reunification Germany. We also find substantial and long-lasting economic effects of Stasi surveillance, resulting in lower income, higher exposure to unemployment, and lower self-employment.
Keywords: H11; N34; N44; P20; 330; Civic capital; government surveillance; trust; economic performance; East Germany